2017
DOI: 10.1177/1758998317720951
|View full text |Cite
|
Sign up to set email alerts
|

Novice therapists in a developing context: Extending the reach of hand rehabilitation

Abstract: Introduction: Hand rehabilitation needs in some parts of the world extend beyond the impact of specialised hand therapists. This study aimed to establish what hand rehabilitation services novice occupational therapists in South Africa were providing; the supports and barriers for such services; and, therapists' perceptions of being equipped for hand rehabilitation. Methods: A descriptive cross-sectional study was conducted, and an online questionnaire was sent to all occupational therapists in their first year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 38 publications
3
29
1
Order By: Relevance
“…They also may, or may not, represent those with experience and expertise in this area, although de Klerk 19 reported that more than 90% of therapists with more than five years' experience in hand rehabilitation a worked in the private sector. Furthermore, within the broader study in which this article is situated, CS occupational therapists confirmed the limited availability of hand surgery services and hand rehabilitation expertise in rural and underserved areas of South Africa [8][9] . It can therefore be surmised that many patients requiring this expert service are unlikely to be able to access it, and that services for the majority of the population fall predominantly to novice and inexperienced therapists such as CS occupational therapists.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…They also may, or may not, represent those with experience and expertise in this area, although de Klerk 19 reported that more than 90% of therapists with more than five years' experience in hand rehabilitation a worked in the private sector. Furthermore, within the broader study in which this article is situated, CS occupational therapists confirmed the limited availability of hand surgery services and hand rehabilitation expertise in rural and underserved areas of South Africa [8][9] . It can therefore be surmised that many patients requiring this expert service are unlikely to be able to access it, and that services for the majority of the population fall predominantly to novice and inexperienced therapists such as CS occupational therapists.…”
Section: Introductionmentioning
confidence: 85%
“…The article reports one aspect of a larger study that investigated the extent to which community service occupational therapists are equipped to treat patients with hand impairments. The larger study, parts of which have been published previously 8,9 , captured aspects of the general practice experience of the 2013 Community Service occupational therapists, as well as their perceived preparedness for treating patients with hand impairments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations